Clinical Risk Factors and Perioperative Hematological Characteristics of Early Postoperative Symptomatic Deep Vein Thrombosis in Posterior Lumbar Spinal Surgery. Issue 19 (1st October 2021) - Zhang, Hengyan; Weng, Huiling; Yu, Keyi; Qiu, Guixing
Abstract : Study Design: A retrospective analysis (2015–2019) of data collected from patients who underwent posterior lumbar spinal surgery. Objective: This study aims to identify the incidence, perioperative hematological characteristics, potential prognostic indicators, and risk factors of deep venous thrombosis (DVT) in the lower limbs after posterior lumbar spinal surgery. Eliminating risk factors or taking measures against patients at risk may reduce the incidence of DVT. Summary of Background Data: Deep venous thromboses have been extensively studied in other reconstructive surgeries. Present literatures provide limited evidence for determining the prognostic and risk factors for this complication after spinal surgery. Methods: Patients who underwent posterior lumbar spinal surgery with internal fixation in the Spine Surgery Center of Peking Union Medical College Hospital (PUMCH) were evaluated. The patient demographics, the number of operative segments, the hematological and biochemical parameters on baseline and postoperative day 1, and the presence of DVTs were obtained from all patients. The diagnosis of DVT was established by venous ultrasound when symptomatic. A multivariate logistic regression test was subsequently performed to determine the prognostic indicators and risk factors for DVT. Results: A total of 2053 patients who received lumbar spine procedures were qualified and included. Patients were followed up for 12 weeks. Early symptomatic DVT occurred in 58 individuals (2.39%; 95% confidence interval [CI], 0.4–0.7%). Advanced age, higher preoperative serum D-dimer level, and lower serum potassium level were recognized as independent risk factors for symptomatic DVT. Conclusion: Multiple independent risk factors were identified for early symptomatic DVT after posterior lumbar spine surgery. Postoperative prophylactic anti-coagulation treatment might be warranted for patients with high D-dimer or low potassium levels before the procedure. Level of Evidence: 4 Abstract : This study demonstrated that advanced age, higher preoperative serum D-dimer level, and lower serum potassium level were independent risk factors of symptomatic deep venous thrombosis (DVT) after posterior lumbar procedures. This allows for potential patient stratification for DVT risks, based on the simple serum indicators in the future and prophylactic measures selected.